The Effect of Population, Gross Regional Domestic Product and Inflation on Local Tax Revenues in DKI Jakarta Province - Maria, Sanggam; Arfianti, Rizka Indri (AIBPM Publisher, 2023)
Taxation is the most significant source of state revenues, accounting for the majority of revenue. National development is a current government program, where local development is one of the plans. Local taxes are one of the sources of tax revenue. The realization of local tax collections in DKI Jakarta Province is predicted to have only reached 44% of the objective in September 2022, a 23% decline from 2021. The goal of this research is to determine the impact on the population, gross regional domestic product and inflation on local tax revenues. This is quantitative research that relies on secondary data, namely time series data which is then processed using Microsoft Excel 2019. The techniques utilized for analysis are descriptive statistical analysis and the classical assumption test, and hypothesis test. Based on the results of the analysis population and gross regional domestic product has sufficient evidence of a positive effect on local tax revenues, the government should be able to improve people's welfare and improve the sectors in the gross regional domestic product. Meanwhile, inflation does not have enough evidence of an affect on local tax revenues.